Investigation of Glycosaminoglycans in Urine and Their Alteration in Patients with Juvenile Idiopathic Arthritis - Elżbieta Lato-Kariakin; Kornelia Kuźnik-Trocha; Anna Gruenpeter; Katarzyna Komosińska-Vassev; Krystyna Olczyk; Katarzyna Winsz-Szczotka (Biomolecules, 2023)
(1) Background: In this study, we evaluated the modulation of urine glycosaminoglycans (GAGs), which resulted from etanercept (ETA) therapy in patients with juvenile idiopathic arthritis (JIA) in whom methotrexate therapy failed to improve their clinical condition. (2) Methods: The sulfated GAGs (sGAGs, by complexation with blue 1,9-dimethylmethylene), including chondroitin–dermatan sulfate (CS/DS) and heparan sulfate (HS), as well as non-sulfated hyaluronic acid (HA, using the immunoenzymatic method), were determined in the blood of 89 children, i.e., 30 healthy children and 59 patients with JIA both before and during two years of ETA treatment. (3) Results: We confirmed the remodeling of the urinary glycan profile of JIA patients. The decrease in the excretion of sGAGs (p < 0.05), resulting from a decrease in the concentration of the dominant fraction in the urine, i.e., CS/DS (p < 0.05), not compensated by an increase in the concentration of HS (p < 0.000005) and HA (p < 0.0005) in the urine of patients with the active disease, was found. The applied biological therapy, leading to clinical improvement in patients, at the same time, did not contribute to normalization of the concentration of sGAGs (p < 0.01) in the urine of patients, as well as CS/DS (p < 0.05) in the urine of sick girls, while it promoted equalization of HS and HA concentrations. These results indicate an inhibition of the destruction of connective tissue structures but do not indicate their complete regeneration. (4) Conclusions: The metabolisms of glycans during JIA, reflected in their urine profile, depend on the patient’s sex and the severity of the inflammatory process. The remodeling pattern of urinary glycans observed in patients with JIA indicates the different roles of individual types of GAGs in the pathogenesis of osteoarticular disorders in sick children. Furthermore, the lack of normalization of urinary GAG levels in treated patients suggests the need for continued therapy and continuous monitoring of its effectiveness, which will contribute to the complete regeneration of the ECM components of the connective tissue and thus protect the patient against possible disability.